Chemical and mechanical properties of coconut shell powder (csp) as partially replacement of fine aggregate in mortar - Tan, Shu Mei (2017)
Nowadays, the generation of waste has been increased accordingly. Coconut shell has become the main contributor to the negative effect of environment problem due to poor waste disposal management which annual production of coconut shell waste reaches 3.18 million tonnes. The purpose of this research is to study the partial replacement of fine aggregate with coconut shell powder (CSP) in mortar through experimental works. The main objective is to identify the properties of coconut shell powder mortars. The experiment start with using 0%, 5%, 10% and 20% of CSP replace fine aggregate in mortar mixing. The proportion of sand to cement to water used in mortar mix design is 2.75: 1: 0.6 according to the standard ASTM C1329-05. The fresh and hardened properties tests was carried out for this mortar mix which are flow table test, Vicat test, compressive strength test and total porosity test by using 50mm x 50mm x 50mm cube. The mortar cubes was cured and tested at the age of 7 days, 28 days and 60 days. X-ray Diffraction (XRD), X-ray Florescence (XRF) and Field Emission Scanning Electronic Microscope (FESEM) were also conducted to determine the chemical composition of coconut shell powder and the microstructure of CSP mortar. The result of the flow table test shows the mortar is more workable when the water content is reduced by increasing percentage of CSP in mortar. Moreover, the setting time result of the CSP mortar shows the mortar paste containing of CSP had accelerated the setting time. The result of compressive strength test shows that the 5 CSP mortar has highest compressive strength among all the cubes with CSP replacement which recorded at 17.40 MPa yet lower than control mortar which is 25.17 MPa. The total porosity of mortar increases about 21.54% after replacement of 5% CSP in 28 days. The XRD and XRF tests show that the major component in CSP is organic material which is cellulose-lbeta (C6H10O5). The higher number of pores also observed in 5 CSP mortar from FESEM micrograph which indicates the high percentage of total porosity lead to reduction in compressive strength.